Peripheral Third Cranial Nerve Palsy in A Patient With Pediatric Form of Multiple Sclerosis - Najo, Jomaa; Grace, Adwane; Abdallah, Rahbani (International Journal of Multiple Sclerosis and Related Disorders, 2024)
Multiple Sclerosis has traditionally been considered an inflammatory and autoimmune disease of the central nervous system. However, peripheral cranial nerve involvement has been described previously in eight cases, raising the hypothesis of a disease spectrum between central and peripheral nervous system. We hereby present a case of a 12 years old girl diagnosed with Multiple Sclerosis who presents with complete unilateral third cranial nerve palsy. Complete clinical, laboratory and radiological work-up was consistent with demyelinating disease. We conclude that demyelination in Multiple Sclerosis can affect in some cases both the central and peripheral nervous system.
Keywords: Sclerosis; central nervous system; peripheral cranial nerve; demyelination; autoimmune demyelinating disease